Tertiary education at a glance: China (Global perspectives on higher education, 24,, 2012)
Description Not Provided

Building world-class universities: different approaches to a shared goal (Global perspectives on higher education, 25,, 2013)
Description Not Provided
section 1. Building world-class universities from a national/regional perspective , section 2. Managing world-class universities from an institutional perspective , section 3. Evaluating world-class universities from a ranking/indicator perspective.

The international imperative in higher education (Global perspectives on higher education, 27,, 2013)
Description Not Provided

Internationalisation of African higher education: towards achieving the MDGs (Global perspectives on higher education, 26,, 2013)
Description Not Provided

Globalization and its impacts on the quality of PhD education: forces and forms in doctoral education worldwide (Global perspectives on higher education, Volume 28,, 2014)
Description Not Provided

How world-class Universities affect global higher education: influences and responses (łkGlobal perspectives on higher education, Volume 30,, 2014)
Description Not Provided

Matching visibility and performance: a standing challenge for world-class universities (Global perspectives on higher education, Volume 35,, 2016)
Description Not Provided

Identity and internationalization in Catholic universities: exploring institutional pathways in context (Global perspectives on higher education, Volume 41,, 2018)
Description Not Provided

World-class universities: towards a global common good and seeking national and institutional contributions (Global perspectives on higher education, Volume 42,, 2019)
Description Not Provided

Corruption in higher education: global challenges and responses (Global perspectives on higher education, Volume 46,, 2020)
Description Not Provided

The emergence of the American university abroad (Global perspectives on higher education, 45,, 2020)
Description Not Provided

The global phenomenon of family-owned or managed universities (Global perspectives on higher education, Volume 44,, 2020)
Description Not Provided

Global trends in higher education quality assurance: challenges and opportunities in internal and external quality assurance (Global perspectives on higher education, Volume 48,, 2020)
Description Not Provided

Intelligent internationalization: the shape of things to come (Global perspectives on higher education, Volume 43,, 2020)
Description Not Provided

Refugees and higher education: trans-national perspectives on access, equity, and internationalization (Global perspectives on higher education, Volume 47,, 2020)
Description Not Provided

Building higher education cooperation with the EU: challenges and opportunities from four continents (Global perspectives on higher education, Volume 49,, 2021)
Description Not Provided

Higher education in the next decade: global challenges, future prospects (Global perspectives on higher education, Volume 20,, 2021)
Description Not Provided

World-class universities: global trends and institutional models (Global perspectives on higher education, Volume 51,, 2021)
Description Not Provided